Bacterial Uropathogens and Antibiotic Susceptibility Patterns in Urinary Tract Infections: Cross-sectional Study at a Secondary Hospital in Southeast Bali - I Gede Yogi Prema Ananda; I Kadek Bayu Adhy Candra; Herman Yudawan; I Gusti Lanang Andi Suharibawa; Radika Naufal Hadi Surya (East Asian Journal of Multidisciplinary Research, 2024)
Urinary tract infections (UTIs) are the most common infection in outpatient settings. Although antibiotics are the primary UTIs treatment, the antibiotic resistance threatens its effectiveness, posing a significant risk to public health. This study aims to explore the common bacterial uropathogens in UTIs patients and to plot the antibiotic susceptibility patterns through a cross-sectional retrospective study. Patients provided aseptic urine samples after consenting, which included clean-catch midstream urine and specimens obtained via straight or indwelling catheters, all stored in sterile containers. Escherichia coli was the most prevalent UTI-causing bacteria (29.2%), followed by Klebsiella pneumoniae (20.8%) and Pseudomonas aeruginosa (10%). Among all pathogens, 34.6% were Extended Spectrum β-lactamase (ESBL), including some of Escherichia coli and Klebsiella Pneumoniae. Escherichia coli was the most prevalent UTI-causing bacteria (29.2%), followed by Klebsiella pneumoniae (20.8%) and Pseudomonas aeruginosa (10%).